MANAJEMEN KURIKULUM DAN PEMBELAJARAN BAHASA INDONESIA DI SDIT MUHAMMADIYAH AL KAUTSAR KARTASURA TAHUN 2013/2014 - Juminingsih Juminingsih; Samino Samino (Universitas Muhammadiyah Surakarta, 2015)
The objective of this research was to describe: Curriculum Development and learningIndonesian, Curriculum Implementation in learning Indonesian and Curriculum Evaluation inlearning Indonesian in SDIT Muhammadiyah Al Kautsar Kartasura. This study is a qualitativeresearch. The research approach used in this study is a case study of data collection techniquesused in this study are in-depth interviews, observation, and documentation. In developing thecurriculum SDIT Muhammadiyah Al Kautsar Kartasura have considered the principles orexisting curriculum development theory. These principles are general principles and specifi cprinciples. The general principles include fl exibility, continuity, effectiveness, and practical.Specifi c principles with regard to arranging goals, learning experiences, content and assessment.Learning Curriculum Implementation in Indonesian in SDIT Muhammadiyah Al Kautsar is thecharacter education learning using learning model that is interesting and fun, which can increasethe value of the character of students. Character development curriculum that is implementedinto the learning activities, extra-curricular activities of students, the fl agship program ofthe school, nursery Competition and activities of daily student. Curriculum evaluation todetermine the effectiveness of the curriculum implemented in SDIT Muhammadiyah Al Kautsarin an effort to improve and enhance the curriculum. Aspects of curriculum evaluation in SDITMuhammadiyah Al Kautsar is appropriate stages of curriculum development stage is thedetermination of objectives, planning, testing, fi eld testing, implementation and quality control.